A method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst
By using cheap asphalt and defect engineering technology to prepare defective carbon shell hydrogen evolution electrocatalysts, the problem of insufficient stability and conductivity of existing electrocatalysts in acidic environments is solved, and efficient, stable and economical hydrogen evolution performance is achieved.
Patent Information
- Application Number
- CN202211058451.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-08-31
AI Technical Summary
The existing transition metal compound hydrogen evolution electrocatalysts have poor stability, poor conductivity, and high cost in acidic environments, which limit their commercial applications.
Defective carbon shell hydrogen evolution electrocatalyst is prepared by using inexpensive asphalt as a carbon precursor, combined with in-situ pyrolysis and defect engineering techniques. The method includes hydrothermal reaction, activation treatment and other steps to form a porous defective carbon support with high conductivity and stability.
A hydrogen evolution electrocatalyst with good stability and excellent HER performance in acidic media is achieved, reducing production costs and suitable for industrial production.
Smart Images

Figure CN115287678B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst. Background Art
[0002] Hydrogen energy is considered to be the most promising clean energy due to its high energy density, abundant sources, and clean and pollution-free. However, the traditional hydrogen production method uses high temperature and high pressure to catalytically reform carbon-containing raw materials, which consumes huge amounts of energy and releases a large amount of greenhouse gas CO2. Electrolysis of water to produce hydrogen is an effective way to obtain hydrogen. It is carried out at room temperature and pressure, and the operation process is simple and has no by-products. It can also be used in industrial production of synthetic ammonia, alkyne hydrogenation, aromatic hydrogenation, and hydrodesulfurization. The development of high-performance and stable electrocatalysts is the key to achieving large-scale electrolysis of water to produce hydrogen. Among them, platinum (Pt) has high catalytic activity and electrochemical stability, but the reserves of Pt-based precious metal materials are limited and expensive, which greatly limits its commercial application. Therefore, finding low-cost and efficient electrocatalysts is a top priority.
[0003] In recent years, researchers have developed many novel non-precious metal hydrogen evolution electrocatalysts, such as transition metal oxides, carbides, nitrides and sulfides. Among them, transition metal compound electrocatalysts are expected to replace Pt-based catalysts because of their abundant reserves, excellent performance and suitability for large-scale preparation. However, this type of electrocatalyst still has problems such as high overpotential of hydrogen evolution reaction, poor stability in acidic environment and poor conductivity. The general solution is to combine with carbon-based carriers, which can effectively alleviate the inherent defects of transition metal compound electrocatalysts. Chinese patent CN110624567A discloses a defect-rich oxygen-doped molybdenum disulfide nanosheet hydrogen evolution electrocatalyst synthesized on carbon cloth by a one-step hydrothermal reaction assisted wet chemical corrosion technology using ammonium molybdate tetrahydrate and thiourea as precursors. However, as a carbon matrix, carbon cloth inevitably has uneven distribution of nanosheets and unstable hydrogen evolution performance. Chinese patent CN113403641A discloses a cobalt-molybdenum oxide layer grown on a conductive substrate by solvent thermal coating on a single cobalt nanosheet hydrogen evolution electrocatalyst, which effectively exposes the active sites, but the hardness of the conductive substrate nickel foam decreases after activation, which is not conducive to commercial application. Chinese patent CN108380229B discloses a method of synthesizing a phosphorus-doped cobalt molybdate hydrogen evolution electrocatalyst by hydrothermal-phosphating carbonization treatment of cobalt chloride hexahydrate, ammonium molybdate tetrahydrate and urea. The method is simple to prepare and the materials are easy to obtain. However, the carbon atom surface lacking functional groups has a weak interaction with metal atoms, resulting in a decrease in the stability and conductivity of the electrocatalyst.
[0004] Based on this, the method of improving the stability and conductivity of transition metal compound catalysts by constructing defect-rich carbon coating structures has not yet been developed. Summary of the invention
[0005] In order to overcome the problems of poor stability and poor conductivity of transition metal compound catalysts in the prior art, the present invention provides a method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst.
[0006] The present invention uses cheap asphalt as a carbon precursor. First, the transition metal compound is strongly coupled with the highly conductive carbon substrate through an in-situ pyrolysis process to improve the conductivity of the catalyst and the stability in acidic media. Secondly, a defect-rich carbon carrier is prepared through a series of defect engineering (precursor and defect-causing agent composite, soft template surfactant and etching in different gas atmospheres, etc.). This porous defect carrier is conducive to the rapid transfer of electrons in the catalytic process, the exposure of active sites, and takes into account conductivity and durability. The preparation method is simple, easy to operate, and can be mass-produced industrially.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In one aspect, the present invention provides a method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst, comprising the following steps:
[0009] Step 1: adding toluene to the asphalt raw material for extraction and separation to obtain toluene soluble matter (TS) and toluene insoluble matter (TI); then adding quinoline to the toluene insoluble matter (TI) for extraction and separation to obtain toluene insoluble matter-quinoline soluble matter (TI-QS) and quinoline insoluble matter (QI);
[0010] Step 2: Take one or more of the asphalt group components obtained by the above extraction and separation, mix them evenly with a surfactant, a transition metal salt and a defect-causing agent, and perform a hydrothermal reaction;
[0011] Step 3: Activate the hydrothermal product to obtain a defect-rich carbon shell hydrogen evolution electrocatalyst.
[0012] Furthermore, the asphalt raw material is one or more of coal tar asphalt, natural asphalt, and petroleum asphalt.
[0013] Furthermore, the screening particle size of the asphalt raw material is 1.0 to 3.0 mm.
[0014] Furthermore, the surfactant is one or more of F127, F123, oleic acid, sodium oleate, CTAB, and SDS; and the mass ratio of the surfactant to the asphalt group component is (0.5-4):1.
[0015] Furthermore, the transition metal salt is cobalt phthalocyanine, cobalt bromide, cobalt nitrate, cobalt chloride, cobalt acetate, cobalt citrate, ferrocene, ferric nitrate, ferric bromide, nickel sulfate, nickel nitrate, and nickel acetate; and the mass ratio of the transition metal salt to the asphalt group component is (1-5):10.
[0016] Furthermore, the defect-causing agent is one or more of sulfide, elemental sulfur, thionyl chloride, polyaniline, hydrazine, and triethylamine; and the mass ratio of the defect-causing agent to the asphalt group component is (1-6):1.
[0017] Furthermore, the temperature of the hydrothermal reaction is 150-180° C., and the time is 8-24 hours.
[0018] Furthermore, the activation atmosphere is one or more of nitrogen, iodine vapor, phosphine, hydrogen sulfide, water vapor, and ammonia.
[0019] Furthermore, the activation temperature is 600-900° C., preferably 700-900° C.; the heating rate is 1-8° C. / min, preferably 3-6° C. / min; and the time is 0.5-5 h, preferably 1-3 h.
[0020] Another aspect of the present invention provides a defect-rich carbon shell hydrogen evolution electrocatalyst prepared by the above method, which is a spherical catalyst with a core-shell structure formed by coupling a transition metal and a carbon shell. The defect degree of the defective carbon shell of the catalyst is I D / I G The values are 0.84-1.27.
[0021] Another aspect of the present invention also provides the use of the defect-rich carbon shell hydrogen evolution electrocatalyst in hydrogen production by electrolysis of water.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention uses polycyclic molecule asphalt as a carbon source, which has a large carbon content and high aromaticity, and is a suitable choice for preparing a carbon carrier;
[0024] (2) The present invention innovatively uses a variety of methods such as soft template surfactants, defect-inducing agents and gas etching to construct a defect-rich carbon shell. This porous defect carrier is conducive to the rapid transfer of electrons in the catalytic process, the exposure of active sites, and takes into account both conductivity and durability;
[0025] (3) The defect-rich carbon shell hydrogen evolution electrocatalyst prepared in the present invention has good stability in acidic medium and has excellent HER performance and catalytic activity. When the current density reaches 10 mA cm -2 When the overpotential is 48-135mV, it has good application prospects in the field of energy conversion.
[0026] (4) The present invention uses low-cost asphalt and non-precious metals as raw materials to prepare high value-added hydrogen evolution electrocatalysts, which has a simple process, good economy and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 LSV diagram of defect-rich carbon shell hydrogen evolution electrocatalyst and Pt / C prepared in Example 1;
[0028] Figure 2 Raman test of the defect-rich carbon shell hydrogen evolution electrocatalyst prepared in Example 1 D / I G value;
[0029] Figure 3 This is a scanning electron microscope image of the defect-rich carbon shell hydrogen evolution electrocatalyst prepared in Example 2;
[0030] Figure 4 LSV diagram of defect-rich carbon shell hydrogen evolution electrocatalyst and Pt / C prepared in Example 2;
[0031] Figure 5 Raman test of the defect-rich carbon shell hydrogen evolution electrocatalyst prepared in Example 3 D / I G value;
[0032] Figure 6 This is the IT stability diagram of the defect-rich carbon shell hydrogen evolution electrocatalyst prepared in Example 3 in 0.5M H2SO4 solution. DETAILED DESCRIPTION
[0033] The examples described below are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operating procedures, but do not limit the protection scope of the patent of the present invention. Any technical solution obtained in the form of equivalent replacement or equivalent transformation should fall within the protection scope of the present invention.
[0034] Example 1
[0035] A method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst comprises the following steps:
[0036] Step 1: 5 g of coal tar pitch raw material was sieved into powder with a particle size of 1.0 mm, and toluene was added for extraction and separation to obtain toluene soluble matter (TS) and toluene insoluble matter (TI);
[0037] Step 2: uniformly mix the toluene soluble matter (TS), surfactant F127 (the mass ratio of F127 to TS is 0.5:1), cobalt phthalocyanine (the mass ratio of cobalt phthalocyanine to TS is 1:10) and thioether (the mass ratio of thioether to TS is 1:1), perform hydrothermal carbonization reaction at a temperature of 150° C. for 8 hours, and wash and dry;
[0038] Step 3: The hydrothermal product was placed in a tube furnace, and heated to 700°C at a rate of 3°C / min in an iodine vapor atmosphere, and kept at this temperature for 1 hour. After subsequent cooling, washing, and freeze-drying, a defect-rich carbon shell hydrogen evolution electrocatalyst was obtained. The degree of carbon shell defects was measured by Raman I D / I G The value indicates that I D / I G is 1.27 (see Figure 2 ).
[0039] The defect-rich carbon shell hydrogen evolution electrocatalyst prepared above was subjected to HER performance test. The specific process was as follows: the prepared hydrogen evolution electrocatalyst was evenly dispersed in deionized water and Nafion solution, and after ultrasonication for 30 minutes, the suspension was evenly coated on the surface of the glassy carbon electrode to prepare a working electrode. For comparison, the same method was used to test the HER performance of commercial Pt / C catalyst. The HER performance was evaluated by line sweep voltammetry curve (LSV curve). At a current density of 10 mA cm -2 The overpotential is 48mV (see Figure 1 ).
[0040] Embodiment 2:
[0041] A method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst comprises the following steps:
[0042] Step 1: 7 g of petroleum asphalt raw material was sieved into powder with a particle size of 1.5 mm, and toluene was added for extraction and separation to obtain toluene soluble matter (TS) and toluene insoluble matter (TI);
[0043] Step 2: The toluene insoluble matter (TI), the surfactant F123 (the mass ratio of F123 to TI is 1:1), cobalt bromide (the mass ratio of cobalt bromide to TI is 2:10) and elemental sulfur (the mass ratio of elemental sulfur to TI is 2:1) are uniformly mixed, and a hydrothermal carbonization reaction is carried out at a temperature of 160°C for 10 hours, and then washed and dried;
[0044] Step 3: The hydrothermal product is placed in a tubular furnace, and the temperature is raised to 800°C at a rate of 4°C / min in a phosphine gas atmosphere, and the temperature is kept constant for 2 hours. After subsequent cooling, washing, and freeze-drying, a defect-rich carbon shell hydrogen evolution electrocatalyst is obtained. The catalyst is a spherical catalyst with a core-shell structure (see Figure 3 ), the carbon shell defect degree I D / I G The value is 1.21.
[0045] The defect-rich carbon shell hydrogen evolution electrocatalyst prepared above was subjected to HER performance test, and the specific test process was the same as that in Example 1. The obtained defect-rich carbon shell hydrogen evolution electrocatalyst was subjected to HER performance test at a current density of 10 mA·cm -2 The overpotential is 72.4mV (see Figure 4 ).
[0046] Example 3
[0047] A method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst comprises the following steps:
[0048] Step 1: 8 g of natural asphalt raw material is sieved into powder with a particle size of 2.0 mm, and toluene is added for extraction and separation to obtain toluene soluble matter (TS) and toluene insoluble matter (TI); then quinoline is added to the toluene insoluble matter (TI) for extraction and separation to obtain toluene insoluble matter-quinoline soluble matter (TI-QS) and quinoline insoluble matter (QI);
[0049] Step 2: The toluene insoluble-quinoline soluble matter (TI-QS), surfactant oleic acid (the mass ratio of oleic acid to TI-QS is 2:1), cobalt nitrate (the mass ratio of cobalt nitrate to TI-QS is 3:10) and thionyl chloride (the mass ratio of thionyl chloride to TI-QS is 3:1) are uniformly mixed, and a hydrothermal carbonization reaction is carried out at a temperature of 170°C for 12 hours, and then washed and dried;
[0050] Step 3: The hydrothermal product is placed in a tubular furnace, and the temperature is raised to 900°C at a rate of 5°C / min in a hydrogen sulfide gas atmosphere, and the temperature is kept constant for 3 hours. After subsequent cooling, washing, and freeze-drying, a defect-rich carbon shell hydrogen evolution electrocatalyst is obtained, and the carbon shell defect degree I D / I G The value is 0.94 (see Figure 5 ).
[0051] The defect-rich carbon shell hydrogen evolution electrocatalyst prepared above was subjected to HER performance test, and the specific test process was the same as that in Example 1. The obtained defect-rich carbon shell hydrogen evolution electrocatalyst was subjected to HER performance test at a current density of 10 mA·cm -2 The overpotential is 112.4mV.
[0052] The defect-rich carbon shell hydrogen evolution electrocatalyst prepared above was subjected to an acid stability performance test. The specific test process was as follows: the prepared catalyst was subjected to a 72-hour chronoamperometric stability test in a 0.5 M H2SO4 solution using a three-electrode system. The test results are shown in Figure 6 .
[0053] Example 4
[0054] A method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst comprises the following steps:
[0055] Step 1: 9 g of coal tar pitch raw material is sieved into powder with a particle size of 2.5 mm, and toluene is added for extraction and separation to obtain toluene soluble matter (TS) and toluene insoluble matter (TI); then quinoline is added to the toluene insoluble matter (TI) for extraction and separation to obtain toluene insoluble matter-quinoline soluble matter (TI-QS) and quinoline insoluble matter (QI);
[0056] Step 2: Evenly mix quinoline insoluble matter (QI), surfactant sodium oleate (the mass ratio of sodium oleate to QI is 3:1), cobalt chloride (the mass ratio of cobalt chloride to QI is 4:10) and polyaniline (the mass ratio of polyaniline to QI is 4:1), perform hydrothermal carbonization reaction at a temperature of 180° C. for 14 h, and wash and dry;
[0057] Step 3: The hydrothermal product is placed in a tubular furnace, and the temperature is raised to 8°C at a rate of 3°C / min in a water vapor atmosphere, and the temperature is kept constant for 3 hours. After subsequent cooling, washing, and freeze-drying, a defect-rich carbon shell hydrogen evolution electrocatalyst is obtained, and the carbon shell defect degree I D / I G The value is 0.87.
[0058] The defect-rich carbon shell hydrogen evolution electrocatalyst prepared above was subjected to HER performance test, and the specific test process was the same as that in Example 1. The obtained defect-rich carbon shell hydrogen evolution electrocatalyst was subjected to HER performance test at a current density of 10 mA·cm -2 The overpotential is 60.8mV.
[0059] Example 5
[0060] A method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst comprises the following steps:
[0061] Step 1: 10 g of petroleum asphalt raw material was sieved into powder with a particle size of 3.0 mm, and toluene was added for extraction and separation to obtain toluene soluble matter (TS) and toluene insoluble matter (TI);
[0062] Step 2: weigh the toluene soluble matter (TS), mix it evenly with surfactant CTAB (the mass ratio of CTAB to TS is 4:1), cobalt acetate (the mass ratio of cobalt acetate to TS is 5:10) and triethylamine (the mass ratio of triethylamine to TS is 5:1), perform hydrothermal carbonization reaction at a temperature of 150° C. for 16 hours, and wash and dry;
[0063] Step 3: The hydrothermal product was placed in a tube furnace, and heated to 900°C at a rate of 5°C / min in an NH3 gas atmosphere, and kept at this temperature for 1 h. After subsequent cooling, washing, and freeze-drying, a defect-rich carbon shell hydrogen evolution electrocatalyst was obtained, and the carbon shell defect degree I D / I G The value is 0.94.
[0064] The defect-rich carbon shell hydrogen evolution electrocatalyst prepared above was subjected to HER performance test, and the specific test process was the same as that in Example 1. The obtained defect-rich carbon shell hydrogen evolution electrocatalyst was subjected to HER performance test at a current density of 10 mA·cm -2 The overpotential is 121.3mV.
[0065] Example 6
[0066] A method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst comprises the following steps:
[0067] Step 1: 5 g of natural asphalt raw material was sieved into powder with a particle size of 2.0 mm, and toluene was added for extraction and separation to obtain toluene soluble matter (TS) and toluene insoluble matter (TI);
[0068] Step 2: weigh the toluene insoluble matter (TI), mix it evenly with the surfactant SDS (the mass ratio of SDS to TI is 1:1), cobalt citrate (the mass ratio of cobalt citrate to TI is 2:10) and hydrazine (the mass ratio of hydrazine to TI is 6:1), perform hydrothermal carbonization reaction at a temperature of 160°C for 18h, and wash and dry;
[0069] Step 3: The hydrothermal product was placed in a tubular furnace, and heated to 700°C at a rate of 4°C / min in a nitrogen and iodine vapor atmosphere, and kept at this temperature for 2 hours. After subsequent cooling, washing, and freeze-drying, a defect-rich carbon shell hydrogen evolution electrocatalyst was obtained, and the carbon shell defect degree I D / I G The value is 1.27.
[0070] The defect-rich carbon shell hydrogen evolution electrocatalyst prepared above was subjected to HER performance test, and the specific test process was the same as that in Example 1. The obtained defect-rich carbon shell hydrogen evolution electrocatalyst was subjected to HER performance test at a current density of 10 mA·cm -2 The overpotential is 135mV.
[0071] Example 7
[0072] This embodiment is a variation of embodiment 1, and the only variation is that the cobalt phthalocyanine in step 1 is replaced by ferrocene, and the hydrothermal carbonization reaction temperature is 150° C. and the reaction time is 24 h.
[0073] Example 8
[0074] This embodiment is a variation of Embodiment 1, and the only variation is that the cobalt phthalocyanine in step 1 is replaced by nickel sulfate.
[0075] Example 9
[0076] This embodiment is a variation of Embodiment 1, and the only variation is that the cobalt phthalocyanine in step 1 is replaced by ferric nitrate.
[0077] Example 10
[0078] This embodiment is a variation of embodiment 1, and the only variation is that the cobalt phthalocyanine in step 1 is replaced by ferric bromide.
[0079] Embodiment 11
[0080] This embodiment is a variation of Embodiment 1, and the only variation is that the cobalt phthalocyanine in step 1 is replaced by nickel nitrate.
[0081] Example 12
[0082] This embodiment is a variation of Embodiment 1, and the only variation is that the cobalt phthalocyanine in step 1 is replaced by nickel acetate.
[0083] The present invention has many implementation modes, and the scope of the claims of the present invention is not limited to the aforementioned specific implementation modes. All technical solutions formed by equivalent transformations are within the protection scope of the present invention.
Claims
1. A method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst, characterized in that: The following steps are involved: Step 1: adding toluene to the asphalt raw material for extraction and separation to obtain toluene soluble matter and toluene insoluble matter; then adding quinoline to the toluene insoluble matter for extraction and separation to obtain toluene insoluble matter-quinoline soluble matter and quinoline insoluble matter; Step 2: Take one or more of the asphalt group components obtained by the above extraction and separation, mix them evenly with a surfactant, a transition metal salt and a defect-causing agent, and perform a hydrothermal reaction; Step 3: activating the hydrothermal product to obtain a defect-rich carbon shell hydrogen evolution electrocatalyst; The surfactant is one or more of F127, F123, oleic acid, sodium oleate, CTAB, and SDS; the defect-causing agent is one or more of thioether, elemental sulfur, thionyl chloride, polyaniline, hydrazine, and triethylamine; the activation atmosphere is one or more of nitrogen, iodine vapor, phosphine, hydrogen sulfide, water vapor, and ammonia; the activation temperature is 600-900°C, the heating rate is 1-8°C / min, and the time is 0.5-5 h.
2. The method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst according to claim 1, characterized in that: The asphalt raw material is one or more of coal tar asphalt, natural asphalt and petroleum asphalt.
3. The method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst according to claim 1, characterized in that: The mass ratio of the surfactant to the asphalt group component is (0.5-4):
1.
4. The method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst according to claim 1, characterized in that: The transition metal salt is cobalt phthalocyanine, cobalt bromide, cobalt nitrate, cobalt chloride, cobalt acetate, cobalt citrate, ferrocene, ferric nitrate, ferric bromide, nickel sulfate, nickel nitrate, and nickel acetate; the mass ratio of the transition metal salt to the asphalt group component is (1-5):
10.
5. The method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst according to claim 1, characterized in that: The mass ratio of the defect-causing agent to the asphalt group component is (1-6):
1.
6. The method for preparing a defect-rich carbon shell hydrogen evolution electrocatalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 150-180° C. and the time is 8-24 h.
7. A defect-rich carbon shell hydrogen evolution electrocatalyst prepared by the method of any one of claims 1 to 6, characterized in that: The defect-rich carbon shell hydrogen evolution electrocatalyst is a spherical catalyst with a core-shell structure formed by coupling a transition metal and a carbon shell. The defect degree of the defective carbon shell of the catalyst is obtained by Raman test. D / I G The values are 0.84-1.
27.
8. Use of a defect-rich carbon shell hydrogen evolution electrocatalyst prepared by the method of any one of claims 1 to 6 or a defect-rich carbon shell hydrogen evolution electrocatalyst according to claim 7, characterized in that: Used in hydrogen production by water electrolysis.
Citation Information
Patent Citations
A method for preparing a phosphorus-doped cobalt molybdate electrocatalyst for hydrogen evolution and its product.
CN108380229B
Electrocatalyst for hydrogen evolution and preparation method and application thereof
CN110624567A
Electrocatalytic material and preparation method and application thereof
CN113403641A
Method for preparing nitrogen-doped porous carbon from heavy organic component in coal liquefaction residue
CN103288070A
Preparation method and application of high-specific-surface porous carbon modified by coal-tar pitch
CN107902654A